1998
DOI: 10.1002/tl.7408
|View full text |Cite
|
Sign up to set email alerts
|

Portfolios: Purposeful Collections of Student Work

Abstract: For many professors, portfolios are flexible enough to serve their own purposes as well as the purposes of the curriculum. Portfolios also meet the current call for authentic assessment of students' skills and performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…These same positive and negative findings have been reported throughout the portfolio literature. 9,35 Certain limitations of our study must be acknowledged when considering the implications of its results. The most obvious limitation relates to sample size.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These same positive and negative findings have been reported throughout the portfolio literature. 9,35 Certain limitations of our study must be acknowledged when considering the implications of its results. The most obvious limitation relates to sample size.…”
Section: Discussionmentioning
confidence: 92%
“…7 Several barriers to implementation of portfolio assessment have been identified, with time being one of the largest. 8,9 Portfolio assessment demands a large time commitment from both faculty and students. Another barrier relates to power and control in the educational environment.…”
mentioning
confidence: 99%
“…aim, some information of portfolio such as definition, types of portfolio and its advantage and disadvantage were discussed in depth. Studying teachers' perceptive of portfolio assessment is important because evidence suggests that teachers' understandings of teaching and learning strongly influence how they teach and what students learn and achieve (Frohbieter, Greenwald, Stecher, and Schwartz, 2011;Mullin, 1998;Wiliam, 2010). To illustrate Samad, Hussin, and Sulaiman's (2015) case study of assessment in Secondary School English classes revealed an eclectic array of conflicting assessment practices, seemingly because the teachers held differing perceptions of teaching and student learning.…”
Section: Research Problemmentioning
confidence: 99%
“…Öğrenciler bazen nelerin yapılacağı veya biriktirileceği konusunda şüpheye düşebilir ya da biriktirme işlemleri için tanınan sürenin yeterli olmayacağı endişesine kapılabilirler (Fenwick ve Parsons, 1999). Her derse biriktirilen malzemeleri getirmelerini istemek öğrencileri sıkıntıya sokabilir veya getirmelerine rağmen üzerinde çalışılmaması ya da çalışılabilmesi için yeterli sürenin ayrılmaması sorun yaratabilir (Mullin, 1998). Biriktirilenler arasında öğrencinin çabasını temsil etmeyen ürünler yer alabilir veya kimi ürünler öğrenme amaçlarıyla yeterince örtüşmeyebilir (Arter ve Spandel, 1992).…”
Section: Portfolyo Değerlendirmeunclassified